Respuesta :
Treat the inequality symbol as if it were an equal sign.
(m / 3) - 3 < -6
m / 3 < -3
m < -9
m3 - 9 <---------------------Answer.
Reformatting the input :
(1): "m3" was replaced by "m^3".
Step by step solution :
Step 1 :
Trying to factor as a Difference of Cubes:
1.1 Factoring: m3-9
Theory : A difference of two perfect cubes, a3 - b3 can be factored into
(a-b) • (a2 +ab +b2)
Proof : (a-b)•(a2+ab+b2) =
a3+a2b+ab2-ba2-b2a-b3 =
a3+(a2b-ba2)+(ab2-b2a)-b3 =
a3+0+0+b3 =
a3+b3
Hope it helped you :)
Awe.